Variedades de Einstein compactas com curvatura isotrópica positiva - Lavor, Otávio Paulino (2013)
The aim of this work is to study compact Einstein manifolds with positive isotropic curvature. More precisely, we shall prove that every compact Einstein manifold with positive isotropic curvature has constant sectional curvature.